Family risk and early attachment development: The differential role of parental sensitivity. Issue 2 (12th January 2022) - Gerlach, Jennifer; Fößel, Judith M.; Vierhaus, Marc; Sann, Alexandra; Eickhorst, Andreas; Zimmermann, Peter; Spangler, Gottfried
Abstract: Family risks are known to be detrimental to children's attachment development. This study investigated whether parental sensitivity plays different roles in early attachment development in the context of risk: Sensitivity was hypothesized to mediate risk effects on attachment, as well as a moderator that shapes the relation between risk and attachment. Multiple family risks, parental sensitivity (defined as responsivity and supportive presence), and children's attachment security of 197 infants and toddlers ( Mage  = 15.25 months) and their caregivers were assessed in a prospective study with a cohort‐sequential‐design in Germany. Caregivers' sensitivity served as a mediator of risk effects on attachment as well as a moderator that buffers adverse consequences of risk. Early sensitivity might be relevant in setting the stage for attachment development supporting resilience. Resumen: A los riesgos familiares se les conoce como perjudiciales para el desarrollo de la afectividad en los niños. Este estudio investigó si la sensibilidad del progenitor juega diferentes papeles en el temprano desarrollo de la afectividad en el contexto de riesgo: La hipótesis es que la sensibilidad sirve de intermediaria de los efectos del riesgo sobre la afectividad, y también como una moderadora que moldea la relación entre el riesgo y la afectividad. Los riesgos familiares múltiples, la sensibilidad del progenitor (definida como la presencia de receptividad y apoyo) y la seguridad de la afectividad del niño en 197 infantes y niños pequeñitos (M = 15.25 meses) y de quienes les cuidaban fueron evaluadas en un estudio de probabilidad con un diseño secuencial de grupo en Alemania. La sensibilidad de quien presta el cuidado sirvió como mediadora de los efectos del riesgo sobre la afectividad, así como también de moderadora que amortigua las consecuencias adversas del riesgo. La temprana sensibilidad pudiera ser relevante para sentar las bases de la fortaleza de resistencia de apoyo al desarrollo de la afectividad. Résumé: Les risques de la famille sont connus comme étant préjudiciables au développement de l'attachement des enfants. Cette étude s'est attachée à étudier si la sensibilité parentale joue des rôles différents dans le développement précoce de l'attachement dans le contexte de risque: on a pris comme hypothèse que la sensibilité a servi de médiatrice aux effets de risque sur l'attachement, et a également servi de modératrice qui forme la relation entre le risqué et l'attachement. Les risques familiaux multiples, la sensibilité parentale (définie comme réceptivité et présence de soutien), et la sécurité de l'attachement de 197 nourrissons et jeunes enfants (M = 15, 25 mois) et des personnes prenant soin d'eux ont été évalués dans une étude prospective avec un plan séquentiel‐cohorte, en Allemagne. La sensibilité de la personne prenant soin de l'enfant a servi de médiateur pour les effets de risque sur l'attachement ainsi que de modérateur qui amorti les conséquences adverses de risque. La sensibilité précoce peut s'avérer pertinente dans la préparation du terrain pour le développement de l'attachement qui souvient la résilience. Zusammenfassung: Familiäre Risiken und frühe Bindungssicherheit: Die unterschiedliche Rolle der elterlichen Sensibilität Es ist bekannt, dass sich familiäre Risiken nachteilig auf die Bindungsentwicklung von Kindern auswirken. In dieser Studie wurde untersucht, ob die elterliche Sensibilität im Kontext von Risiken bei der frühen Bindungsentwicklung eine unterschiedliche Rolle spielt: Es wurde die Hypothese aufgestellt, dass Sensibilität die Auswirkungen von Risiken auf die Bindung mediiert und als Moderator die Beziehung zwischen Risiko und Bindung beeinflusst. In einer prospektiven Studie mit kohortensequentiellem Design in Deutschland wurden 197 Säuglinge und Kleinkinder (M = 15, 25 Monate) und ihre Bezugspersonen hinsichtlich mehrerer familiärer Risiken, elterlicher Sensibilität (definiert als Responsivität und unterstützende Präsenz) und der Bindungssicherheit der Kinder untersucht. Die Sensibilität der Bezugsperson diente als Mediator von Risikoeffekten auf die Bindung sowie als Moderator, der die negativen Folgen des Risikos abpuffert. Frühe Sensibilität könnte eine wichtige Rolle bei der Schaffung von Voraussetzungen für eine Bindungsentwicklung spielen, die Resilienz unterstützt. 抄録: 家庭リスクと幼少期のアタッチメントの安定性:親の敏感性の役割の違い 家庭リスクは、子どものアタッチメント形成に悪影響を及ぼすことが知られている。本研究では、親の敏感性が初期のアタッチメント形成において、リスクの文脈で異なる役割を果たしているかどうかを検討した。敏感性は、リスクとアタッチメントの関係を形成するモデレーター (仲介者) であると同時に、アタッチメントに対するリスク効果を媒介すると仮定した。本研究では、ドイツの197名の乳幼児 (平均月齢15.25ヶ月) とその養育者を対象に、多重家庭リスク、親の敏感性 (応答性と支援的存在として定義) 、および子どものアタッチメントの安定性を、コホート・シークエンシャル・デザインを用いて前向き研究で評価した。養育者の敏感性は、アタッチメントに対するリスク効果の媒介役割とともに、リスクの悪影響を緩和するモデレーターの役割を果たしていることがわかった。早期の敏感性は、レジリエンスを支えるアタッチメント発達の土台をつくることに関係している可能性がある。 摘要: 众所周知, 家庭风险不利于儿童的依恋发展。本研究调查了父母敏感性是否在风险背景下的早期依恋发展中发挥了不同的作用:假设敏感性可以调节依恋的风险影响, 也可以调节风险与依恋之间的关系。在德国采用群组序列设计的前瞻性研究中, 对197名婴幼儿 (M = 15.25个月) 及其看护者的多重家庭风险、父母敏感性 (定义为响应性和支持性存在) 以及儿童依恋安全进行了评估。看护者的敏感性是依恋风险影响的调节因素, 也是缓冲风险不利后果的调节因素。早期敏感性或许可以为提高复原力的依恋发展奠定基础。 ملخص: مخاطر الأسرة وأمان التعلق المبكر: الدور المتغير لحساسية الوالدين من المعروف أن المخاطر العائلية تضر بتطور تعلق الأطفال. استقصت هذه الدراسة ما إذا كانت حساسية الوالدين تلعب أدوارًا مختلفة في تطوير التعلق المبكر في سياق المخاطر: تم افتراض الحساسية للتوسط في تأثيرات المخاطر على التعلق ، بالإضافة إلى كونها عامل وسيط يشكل العلاقة بين المخاطرة والتعلق. تم تقييم المخاطر العائلية المتعددة ، والحساسية الأبوية (التي تُعرَّف على أنها الاستجابة والحضور الداعم) ، وأمان تعلق الأطفال عند197 رضيعًا وطفلًا صغيرًا (M = 15.25 شهرًا) ومقدمي الرعاية لهم في دراسة استطلاعية ذات تصميم مجموعات متسلسل في ألمانيا. عملت حساسية مقدم الرعاية كوسيط لتأثيرات المخاطر على التعلق وكذلك الوسيط الذي يخفف من الآثار السلبية للمخاطر. توصلت الدراسة إلى أن الحساسية المبكرة قد تكون ذات صلة في تمهيد الطريق لنمو التعلق الذي يدعم المرونة.